+0  
 
+6
143
1
avatar+152 

Explain this to me please.

\(\frac{m-3}{4}=\frac{m+1}{3}\)

xRainexSiderisx  Mar 9, 2017

Best Answer 

 #1
avatar+79716 
+10

[m - 3] / 4   = [m + 1 ] / 3        cross-multiply

 

3 [ m - 3 ]  = 4 [ m + 1]       simplify

 

3m - 9    =  4m + 4     add 9 to both sides, subtract 4m from both sides

 

-1m   =  13          divide both sides by -1

 

m = -13

 

 

cool cool cool

CPhill  Mar 9, 2017
Sort: 

1+0 Answers

 #1
avatar+79716 
+10
Best Answer

[m - 3] / 4   = [m + 1 ] / 3        cross-multiply

 

3 [ m - 3 ]  = 4 [ m + 1]       simplify

 

3m - 9    =  4m + 4     add 9 to both sides, subtract 4m from both sides

 

-1m   =  13          divide both sides by -1

 

m = -13

 

 

cool cool cool

CPhill  Mar 9, 2017

19 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details